REQUIREMENTS TO TEACHERS’ DIGITAL COMPETENCE TODAY - Svetlana V. Titova; Anna P. Avramenko (Высшее образование в России)
ICT and mobile technologies integration into teaching context is one of the pivotal trends of modernization of higher education system in Russian Federation. Nowadays language teachers need to be not only computer literate but also to have professional confidenceto use digital technologies and resources adequately and methodologically correctly. Thispaper focuses on the analysis of digital competence structure according to new educational standards designed by both Russian and foreign recognized bodies and specialists. The paper also reports on the research that was undertaken by the authors and based on qualitative and quantitative data collected from the Russian and Norwegian university teachers in 2012-2013. The objectives of the research are to analyze Russian and Norwegian teachers’ experience in mobile technologies integration, to define some perspectives of new technologies use aseducational tools for enhancing learners’ output and to determine what mobile applications are most appropriate to support learning context today.